TRAINING ON BIOCHEMICHAL IDENTIFICATION OF ENTEROBACTERIACEAE USING THE ENTEROSYSTEM 24R KIT TO STUDENTS OF MEDICAL LABORATORY TECHNOLOGY AT YARSI MEDIKA VOCATIONAL HIGH SCHOOL, TANGERANG - Pangeran Andareas; Maroloan Aruan; Diana Intan Gabriella Lusiana; Maleakhi Samuel Mardiyono; Dolito Situmorang; Naomi Damayanti Purba; Nava Anabel Tahalele (Universitas Pelita Harapan, 2024)
Tri Dharma Perguruan Tinggi is the main foundation for universities in Indonesia in carrying out their functions and responsibilities. One of the activities that is part of the Tri Dharma of Higher Education is Community Service (CS). PkM activities have the aim of improving the welfare of the community by providing solutions to various problems that exist in the community. One solution that can be provided is to provide training to the community with the aim of increasing knowledge, skills or competencies of human resources (HR). One of the important communities to improve competence is school students, especially vocational high schools (VHS) majoring in medical laboratory technology (MLT). This activity is important so that the graduates produced are in accordance with the needs of the world of work such as hospitals, clinics and research institutions. This activity was given to students majoring in medical laboratory technology, VHS Yarsi Medika Tangerang. The topic raised in this activity is training in the identification of enterobacteriaceae using the Enterosystem 24R kit. The data in this activity was obtained with a Quiz instrument (Pre-Test and Test) using Google Form. The results obtained from PkM activities show that there is an increase in student knowledge related to PkM material by 35%.